Integrating Service-Learning in the Public Speaking Course - Elizabeth A. Munz; Roger D. Gatchet; Matthew R. Meier (Central States Communication Association, 2018)
This best-practices article endorses incorporating service-learning into the foundational public speaking course. The article explains connections between service-learning and the rhetorical tradition, highlights pedagogical approaches that would benefit from a service-learning component, and discusses the benefits of service-learning for community partners and students. The remainder of the article focuses on how to implement service learning in a public speaking course, including reflection and assessment recommendations.